The Impact of Palliative Transurethral Resection of the Prostate on the Prognosis of Patients With Bladder Outlet Obstruction and Metastatic Prostate Cancer: A Population-Matched Study - Fang, Kun; Song, Pan; Zhang, Jiahe; Yang, Luchen; Liu, Peiwen; Lu, Ni; Dong, Qiang (Frontiers in Surgery, 2021)
Objective: The aim of this study was to evaluate the survival outcomes of patients with bladder outlet obstruction (BOO) and metastatic prostate cancer (mPCa) after the surgery of palliative transurethral resection of the prostate (pTURP). Methods: We identified patients with mPCa between 2004 and 2016 in the Surveillance, Epidemiology and End Results (SEER) database. The patients who received pTURP and non-surgical therapy were identified. The propensity-score matching was introduced to balance the covariate. Kaplan–Meier analysis and Cox regression were conducted to evaluate the overall survival (OS) and cancer-specific survival (CSS) outcomes. Results: A total of 36003 patients were identified. 2823 of them were in the pTURP group, 33180 in the non-surgical group. The survival curves of the overall cohort showed that pTURP group was associated with worse outcomes of both OS (HR: 1.12, 95%CI: 1.07~1.18, p<0.001) and CSS (HR: 1.08, 95%CI: 1.02~1.15, p=0.004) in the comparison of non-surgical group. The mean survival time in overall cohort of pTURP group was shorter than non-surgical group in OS [35.13±1.53 vs 40.44±0.59 months] and CSS [48.8±1.27 vs 55.92±0.43 months]. In the matched cohort, pTURP group had significantly lower survival curves of both OS (HR: 1.25, 95%CI: 1.16~1.35, p<0.001) and CSS (HR: 1.23, 95%CI: 1.12~1.35, p<0.001) than non-surgical group. pTURP significantly reduced the survival months (36.49±0.94 vs 45.52±1.23 months in OS and 50.1±1.49 vs 61.28±1.74 months in CSS). In multivariate COX analysis, pTURP increased the risk of overall mortality (HR: 1.19, 95%CI: 1.09~1.31, p<0.001) and cancer-specific mortality CSS (HR: 1.23, 95%CI: 1.14~1.33, p<0.001) than the non-surgical group.